2019
DOI: 10.1111/jocn.15026
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related fatigue and self‐care agency: A multicentre survey of patients receiving chemotherapy

Abstract: Aims and objectives To measure cancer‐related fatigue (CRF), self‐care agency (SCA) and fatigue self‐care strategies, and to explore the relationship between CRF and SCA. Background Cancer‐related fatigue has been consistently rated as the most elusive, common and severe of symptoms that patients with cancer undergoing chemotherapy experience. Despite its frequency and severity, CRF is poorly managed. A renewed focus on supporting self‐care among patients with cancer has been found to reduce symptom burden, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 50 publications
3
14
0
1
Order By: Relevance
“…In the present study, 69% of the lymphoma patients experienced fatigue. A previous study also highlighted that the odds of experiencing fatigue were three times among lymphoma patients receiving chemotherapy compared to those with other types of cancers (O'Regan et al, 2019). Additionally, approximately 19% of patients complained of severe fatigue in the current study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the present study, 69% of the lymphoma patients experienced fatigue. A previous study also highlighted that the odds of experiencing fatigue were three times among lymphoma patients receiving chemotherapy compared to those with other types of cancers (O'Regan et al, 2019). Additionally, approximately 19% of patients complained of severe fatigue in the current study.…”
Section: Discussionsupporting
confidence: 55%
“…Several prior studies have shown that CRF in cancer patients has a serious negative impact on physical and psychological well-being (Bevans & Sternberg, 2012;O'Regan et al, 2019), thus affecting the overall quality of life. Similar results were reported in a survey conducted in the United States on 379 cancer patients; 91% of the participants claimed that fatigue impacted their normal life (Curt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelelahan perilaku merupakan penurunan fungsional yang dapat mempengaruhi kualitas hidup. Kelelahan pada pasien kanker dapat berdampak pada perilaku perawatan diri pasien (O'Regan et al, 2019). Wang et al, (2020) menggambarkan bahwa kemampuan perawatan diri yang baik dikaitkan dengan kelelahan yang lebih rendah.…”
Section: Pembahasanunclassified
“…Cancer treatments can produce debilitating symptoms that have a profound impact on patients’ quality of life. The most common, severe, and consistently reported side effect of chemotherapy is fatigue ( O’Regan et al, 2019 ), which is defined as a sense of tiredness or exhaustion that is not proportional to activity nor sleep. No approved therapies for cancer-related fatigue (CRF) have been developed, in part because the etiology explaining the development of the symptom is poorly understood.…”
Section: Introductionmentioning
confidence: 99%